Perspektif Masyarakat Hatunuru Terhadap Ceritera Rakyat Danau Tapala dan Manfaatnya Bagi Masyarakat Di Kecamatan Taniwel Timur Kabupaten Seram Bagian Barat - Solehuwey, Sintia; Touwe, Sem; Acim, Acim (Program Studi Pendidikan Sejarah, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Pattimura, 2023)
This paper examines several key issues, namely: 1) How the formation of Lake Tapala occurred, 2) The perspective of the Hatunuru community on the myth of Lake Tapala in the Taniwel Timur District, and 3) The benefits of Lake Tapala for the Hatunuru community. This research uses a descriptive qualitative method to produce descriptive data, analysis, and interpretation in the form of written or spoken words from people and observed behaviours. The study results indicate that the Hatunuru community perceives the formation of Lake Chapala as a strategic and crucial historical event experienced by their ancestors. Additionally, the community views the utilization of Lake Tapala in economic, socio-cultural, and tourism development aspects as a fundamental need that should be actively promoted in various sectors.